FUNCTIONAL STATUS OF METABOLIC COMPONENT OF CELLULAR ENERGY METABOLISM BY COMMUNITY-ACGUIRED PNEUMONIA IN CHILDREN WITH PERINATAL AFFECTION OF CNS - Гончарова, Татьяна Александровна (Mother and Baby in Kuzbass, 2018)
The aim of this study – to investigate the characteristics of the functional state of the metabolic level of cell energy metabolism in uncomplicated and complicated community-acquired pneumonia in children with perinatal CNS involvement.Materials and methods. There were examined 87 children aged from 6 months to 3 years with community-acquired pneumonia (CAP) and associated CNS involvement. The patients were divided into 2 groups. The I group consisted of 44 children (56,6 %) with complicated course of CAP. The II group consisted of 43 patients (49,4 %) with uncomplicated pneumonia. Under the data of content of lactate and pyruvate in blood there was determined the character of disorders of metabolic level of cell energy metabolism. The automated biochemical analyzer COBAS INTEGRA 400 plus and a spectrophotometer PE-5300 VI were used in the study.Results and their discussion. The average values of the content of lactate and pyruvate in blood and determination of their ratio in patients in both groups showed that the greatest coefficient value (20,4 ± 0,72) was among children with perinatal CNS involvement, who had the severe complicated course the pneumonia. In the group of patients with uncomplicated CAP course test cvharacteristic was 16.2 ± 0,49 (p < 0.001) and in the control group – 9.8 ± 0,30.Conclusion. In complicated pneumonia dominant metabolism is anaerobic glycolysis indicating decompensation of energy homeostasis of patients` body, as well as attributable to them expressed metabolic disorders in form of lactat acid acidosis along with hypoxemia, hypercapnia.
Keywords: community-acquired pneumonia; young children; perinatal CNS damage; lactate; pyruvate